Editorial for the Special Issue on Organs-on-Chips - Yu-suke Torisawa; Yi-Chung Tung (Micromachines, 2020)
Recent advances in microsystems technology and cell culture techniques have led to the development of organ-on-chip microdevices to model functional units of organs [...]